Impaired Cognitive Function and Hippocampal Changes Following Chronic Diazepam Treatment in Middle-Aged Mice - Furukawa, Tomonori; Nikaido, Yoshikazu; Shimoyama, Shuji; Masuyama, Nozomu; Notoya, Ayaka; Ueno, Shinya (Frontiers in Aging Neuroscience, 2021)
Gamma-aminobutyric acid (GABA) type A receptors are positively allosterically modulated by benzodiazepine binding, leading to a potentiated response to GABA. Diazepam (DZP, a benzodiazepine) is widely prescribed for anxiety, epileptic discharge, and insomnia, and is also used as muscle relaxant and anti-convulsant. However, some adverse effects are elicited by the long-term use of DZP. Clinical studies have reported that chronic DZP treatment increases the risk of dementia in older adults. Furthermore, several studies have reported that chronic DZP administration may affect neuronal activity in the hippocampus, dendritic spine structure, and cognitive performance. However, the effects of chronic DZP administration on cognitive function in aged mice is not yet completely understood. A behavioral test, immunohistochemical analysis of neurogenic and apoptotic markers, dendritic spine density analysis, and long-term potentiation (LTP) assay of the hippocampal CA1 and CA3 were performed in both young and middle-aged mice to investigate the effects of chronic DZP administration on cognitive function. The chronic intraperitoneal administration of DZP was performed by implanting an osmotic minipump. To assess spatial learning and memory ability, the Morris water maze test was performed. Dendritic spines were visualized using Lucifer yellow injection, and spine density was analyzed. Moreover, the effects of exercise on DZP-induced changes in spine density and LTP were assessed. Learning performance was impaired by chronic DZP administration in middle-aged mice but not in young mice. LTP was attenuated by DZP administration in the CA1 of young mice and the CA3 of middle-aged mice. The spine density of hippocampal neurons was decreased by chronic DZP administration in the CA1 of both young and middle-aged mice as well as in the CA3 of middle-aged mice. Neither neurogenesis nor apoptosis in the hippocampus was affected by chronic DZP administration. The results of this study suggest that the effects of chronic DZP are different between young and middle-aged mice. The chronic DZP-induced memory retrieval performance impairment in middle-aged mice can likely be attributed to decreased LTP and dendritic spine density in hippocampal neurons in the CA3. Notably, prophylactic exercise suppressed the adverse effects of chronic DZP on LTP and spine maintenance in middle-aged mice.